The root of development is the innovative mind - Hudson, Colin (Technical Centre for Agricultural and Rural Cooperation, 1993)
Dr Colin Hudson is Chief Executive of Carib Agro-lndustries Ltd of Barbados, which is regarded as one of the leading problem-solving organizations in the Caribbean. He has acted as a consultant on innovative technologies throughout the region and in...